Foundations of Quantum Mechanics - Norsen, Travis (Springer, 2017)
This textbook is intended as a lifeline to physics students (of either the traditional or the autodidactic variety) who have had some preliminary exposure to quantum mechanics but who want to actually try to make physical and conceptual sense of the theory in the same way that they have been trained and expected to do when learning about other areas of physics. Its main goals are (i) to help students appreciate and understand the concerns that people like Einstein, Schrödinger, and Bell have had with traditional formulations of the theory and (ii) to introduce students to the several extant formulations of quantum theory which purport to address at least some of the concerns and provide candidate accounts of what quantum theory might actually imply about how the micro-physical world works. The book grew out of, and its structure in many ways reflects, the “special topics in physics” course on the Foundations of Quantum Mechanics that I taught at Smith College in the Spring of 2016. In this seminar-style course, students would read through each new chapter (and attempt a few of the end-of-chapter Projects that I recommended as appropriate pre-class exercises) prior to our weekly three-hour meeting. During our time together in class, we would discuss the more difficult concepts and derivations from the text, students would share their (sometimes only partial) solutions to the assigned pre-class projects (and we would discuss and complete those as needed), and then we would tackle some additional projects. Not surprisingly, then, I envision the book being most straightforwardly useful for a similarly structured elective course in a physics department (or perhaps for a philosophy-of-physics course focused on the Foundations of Quantum Mechanics in a philosophy department). But the fact that the chapters were created as pre-class readings (as opposed to transcripts of “lecture notes”) perhaps makes this, compared to most physics textbooks, unusually readable and accessible to individuals for whom it is not the textbook for any official course—e.g., interested physics students who are not lucky enough to find themselves in a department that offers an elective course on the Foundations of Quantum Mechanics, or just anyone with an interest in the puzzling and fascinating history, philosophy, and, really, physics of quantum physics.
An Exploration of the Physical Meaning of Quantum Theory